Mixed-mode high-power impulse magnetron sputter deposition of tetrahedral amorphous carbon with pulse-length control of ionization - Tucker, Mark; Ganesan, R.; McCulloch, D.; Partridge, J.; Stueber, M.; Ulrich, S.; Bilek, M.; McKenzie, D.; Marks, Nigel (American Institute of Physics, 2016)
© 2016 Author(s). High-power impulse magnetron sputtering (HiPIMS) is used to deposit amorphous carbon thin films with sp3 fractions of 13% to 82%. Increasing the pulse length results in a transition from conventional HiPIMS deposition to a "mixed-mode" in which an arc triggers on the target surface, resulting in a large flux of carbon ions. The films are characterized using X-ray photoelectron spectroscopy, Raman spectroscopy, ellipsometry, nanoindentation, elastic recoil detection analysis, and measurements of stress and contact angle. All properties vary in a consistent manner, showing a high tetrahedral character only for long pulses, demonstrating that mixed-mode deposition is the source of the high carbon ion flux. Varying the substrate bias reveals an "energy window" effect, where the sp3 fraction of the films is greatest for a substrate bias around -100 V and decreases for higher or lower bias values. In the absence of bias, the films' properties show little dependence on the pulse length, showing that energetic ions are the origin of the highly tetrahedral character.